2009
DOI: 10.1021/jf803011r
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Antioxidant Properties and Total Phenolic Content of 30 Plant Extracts of Industrial Interest Using DPPH, ABTS, FRAP, SOD, and ORAC Assays

Abstract: Aqueous extracts of 30 plants were investigated for their antioxidant properties using DPPH and ABTS radical scavenging capacity assay, oxygen radical absorbance capacity (ORAC) assay, superoxide dismutase (SOD) assay, and ferric reducing antioxidant potential (FRAP) assay. Total phenolic content was also determined by the Folin-Ciocalteu method. Antioxidant properties and total phenolic content differed significantly among selected plants. It was found that oak (Quercus robur), pine (Pinus maritima), and cinn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

105
867
14
25

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,445 publications
(1,011 citation statements)
references
References 42 publications
105
867
14
25
Order By: Relevance
“…In this study the ORAC method was chosen since it is presently the only antioxidant capacity assay that measures the complete reaction between reactive species and antioxidants taking into account both time and degree of inhibition (Cao & Prior, 1999;Prior, Wu, & Schaich, 2005;Dudonne, Vitrac, Coutiere, Woillez, & Merillon, 2009), thus it is the most recommended method for food samples where complex reaction kinetics occur (Huang, Ou, & Prior, 2005). Significant differences were observed among the varieties investigated.…”
Section: Total Antioxidant Capacity (Tac) -Oracmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study the ORAC method was chosen since it is presently the only antioxidant capacity assay that measures the complete reaction between reactive species and antioxidants taking into account both time and degree of inhibition (Cao & Prior, 1999;Prior, Wu, & Schaich, 2005;Dudonne, Vitrac, Coutiere, Woillez, & Merillon, 2009), thus it is the most recommended method for food samples where complex reaction kinetics occur (Huang, Ou, & Prior, 2005). Significant differences were observed among the varieties investigated.…”
Section: Total Antioxidant Capacity (Tac) -Oracmentioning
confidence: 99%
“…Significant differences were observed among the varieties investigated. The seeds of Deglet Nour and Khoaut Allig had similar values of 27698 and 26905 µmol TE 100 g −1 of DSP on FW basis, whereas significantly lower amounts (P ≤ 0.05) were detected in Zahidi (12540 µmol TE 100 g −1 of DSP on For future studies, the use of more than one single approach for TAC determination is recommended in order to take into account the diverse mechanisms of action of antioxidants (Huang et al, 2005;Capitani et al, 2009;Dudonne et al, 2009;Tabart et al, 2012). On the other hand, there are still controversies over the significance of current in vitro techniques in predicting the in vivo effects of antioxidant compounds (Serrano, Goni, & Saura-Calixto, 2007) and their functionality in preventing or delaying oxidation in foods (Fernandez-Panchon et al, 2008;Alamed, Chaiyasit, McClements, & Decker, 2009).…”
Section: Total Antioxidant Capacity (Tac) -Oracmentioning
confidence: 99%
“…Several studies on yerba maté have reported the presence of xanthines such as caffeine and theobromine, saponines, and several phenolic compounds, mainly chlorogenic acids and dicaffeoylquinic acid derivatives (FILIP et al, 2000;SCHINELLA et al, 2000;RAMIREZ-MARES;BORTOLUZZI et al, 2006;GUGLIUCCI et al, 1996); Dudonne et al (2009) reported 200 mg gallic acid equivalents per g of powder extract and Bravo et al (2007) reported 45 mg caffeoyquinic acids per g of dry samples. It has also been reported that yerba maté extracts have an in vitro antioxidant capacity (AOC), which is due to the presence of polyphenolic compounds that have an antioxidant capacity equal to or higher than that of ascorbic acid and vitamin E (FILIP et al, 2000;SCHINELLA et al, 2000;RAMIREZ-MARES;GUGLIUCCI et al, 1996;GONZALEZ DE MEJIA et al, 2005).…”
mentioning
confidence: 99%
“…The result indicates a strong association between antioxidative activities and phenolic compound, suggesting that phenolic compounds are probably responsible for the antioxidative activities of S. surattense. Phenolic compounds are also effective hydrogen donors, which makes them good antioxidants [30,31] . Thus, the therapeutic properties of S. surattense may be possibly attributed to the phenolic compounds present.…”
Section: Discussionmentioning
confidence: 99%